Trauma and suicide risk in college students: Does lock of agency, lock of pathways, or both add to further risk? - Lucas, Abigael G. et al (Social Work)
The present study sought to examine trauma history and hope as predictors of suicide risk in a sample of 561 college students. Furthermore, authors aimed to understand whether the lack of hope agency and hope pathways contributed to further risk for suicide, above and beyond trauma history. Results suggested that trauma history and hope agency were significant and unique predictors of suicide risk among college students. More specifically, hope agency accounted for additional variance in the prediction model of suicide risk, beyond that accounted for by trauma history. Some implications of the present findings for social work practice are discussed.- Reproduced
Keywords: College students - Mental health, Collage students, Hope, Suicide risk, Tauma history